2012
DOI: 10.1111/j.1365-3113.2012.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and the fossil record of the Helophoridae reveal Jurassic origin of extant hydrophiloid lineages (Coleoptera: Polyphaga)

Abstract: We performed a phylogenetic analysis focused on the hydrophiloid family Helophoridae (Coleoptera: Polyphaga) in order to test the phylogenetic position of selected Mesozoic fossils assigned to the Hydrophiloidea. The analysis is based on 92 characters of larvae and adults, and includes all extant subgenera of Helophorus and representatives of all other extant hydrophiloid families. Based on this analysis, we provide additional evidence for the monophyly of the helophorid lineage containing the families Helopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
2
21
1
Order By: Relevance
“…Our molecular age estimates for Early-Middle Jurassic origins of most major hydrophilid clades are consistent with the fossil record because several modern hydrophiloid families were already well established by the Late Jurassic [21], [47] and Hydrophilidae was worldwide in distribution by the Late Jurassic [48]. Thus, our study provides the most robust temporal framework to date for interpreting the diversification of hydrophiloid water beetles.…”
Section: Discussionsupporting
confidence: 80%
“…Our molecular age estimates for Early-Middle Jurassic origins of most major hydrophilid clades are consistent with the fossil record because several modern hydrophiloid families were already well established by the Late Jurassic [21], [47] and Hydrophilidae was worldwide in distribution by the Late Jurassic [48]. Thus, our study provides the most robust temporal framework to date for interpreting the diversification of hydrophiloid water beetles.…”
Section: Discussionsupporting
confidence: 80%
“…Morphological terminology follows Komarek () and Lawrence et al . (); the term trichobothrium is used for ‘systematic puncture’ sensu Hansen (; see Fikáček et al ., 2012b for details).…”
Section: Methodsmentioning
confidence: 99%
“…Recent revision by Fikáček et al . (2012a) revealed that M. schultzi does not belong to Mesosperchus Ponomarenko, , which is now considered a formal subgenus of Helophorus (Hydrophiloidea: Helophoridae), comprising its Late Jurassic species (Fikáček et al ., 2012a,b). Instead, ‘ Mesosperchus ’ schultzi was shown to resemble modern Hydrophilidae by the shape of the head, presence of the large clypeus and distinct frontoclypeal suture (Fikáček et al ., 2012a).…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations